Entrepreneurial Innovation And Competitive Performance Of Small And Medium Enterprises: Evidence From Emerging Economies - Daniel Oluwaseun Oyalakun; Emmanuel Olusola Ojo; Samuel Olufemi Omoyele; Sekinat Arike Sanni-Bamigbade; Felix Ayotomiwa Olabisi; Comfort Inioluwa Oyalakun (Universitas Indonesia Membangun (Inaba), 2025)
This study examines entrepreneurial innovation as a driving force towards competitive performance in SMEs. The objectives of the study were to determine the effect of product innovation on customer satisfaction, to ascertain the effect of process innovation on customer retention, to establish the effect of market innovation on brand awareness, and to determine the effect of technology innovation on competitive advantage. The population of the study is one hundred and seventy-eight (178) registered SMEs of livestock farms in Ibadan, Oyo State, who deal with animal production, feed formulation and processing, distribution and retail of livestock products, and sales. The study made use of a census survey, due to the very tiny population, in which one hundred and fifty-two (152) was used as the sample size. A questionnaire was used to gather primary data, which was then subjected to regression analysis using the Statistical Package for Social Sciences (SPSS). The findings showed that: market innovation has a significant impact on brand awareness (R2 = 0.880, p < 0.005); product innovation has a significant impact on customer satisfaction (R2 = 0.768, p < 0.005); process innovation has a significant impact on customer retention (R2 = 0.453, p < 0.005); and technology innovation has a significant impact on competitive advantage (R2 = 0.823, p < 0.005). The competitive performance of SMEs was shown to be significantly impacted by entrepreneurial innovativeness, and it is advised that business owners implement a management strategy that makes use of entrepreneurial innovativeness as a tool for boosting firm competitiveness.